APPLICATION OF A COOPERATIVE LEARNING MODEL OF CONCEPT SENTENCE TYPE ASSISTED WITH SERIES OF PICTURES TO IMPROVE PARTICIPANTS' NARRATIVE ESSAY WRITING SKILLS EDUCATION IN CLASS IV SDN 04 CUPAK SOLOK DISTRICT - Rendy Nugraha Frasandy; Elfia Sukma; Hasnah Hasnah; Nyangfah Nisa Septiana (PIONIR: JURNAL PENDIDIKAN, 2024)
Abstract The research was motivated by the results of the writing skills at SDN Solok Regency are still low, found from 27 students as many as 8 students with a percentage of 29.63% reached the KKM and as many as 19 students with a percentage of 70.37% did not reach the KKM. This low skill is caused by educators not providing enough writing training, especially writing narrative essays. The purpose of this study was to improve students' narrative essay writing skills. This research is a field research with the type of research Pre-Experimental Design form One-Group Pretest-Posttest. The data collection techniques and instruments used were tests, observation, and documentation. Data analysis techniques used normality test, homogeneity test and hypothesis testing. The results showed that the post-test score was greater than the pre-test score (79 > 49), obtained t_hitung 26.446 > t_table 2.0555 and Sig. 0.001 < 0.05. This shows that the proposed hypothesis is accepted. It can be concluded that by applying the Concept Sentence type cooperative learning model with the help of serial images can improve the narrative essay writing skills of fourth grade students of SDN Solok Regency.Keywords: Concept Sentence Model, Narrative Writing